Effect of Progressive Muscle Relaxation on Anxiety in Pre-University Students: A Randomized Controlled Clinical Trial - Roozbahani, Tahereh; Nourian, Manijeh; Saatchi, Kiyarash; Moslemi, Azam (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Anxiety experience in adolescents is more intense than other periods of life. The relaxation of muscles leads to the relaxation of the mind, because it prevents the production of negative thoughts. Therefore, this study was done with the purpose of determining the effects of Progressive Muscle Relaxation (PMR) on pre-university students’ anxiety. Methods: In this randomized controlled clinical trial, 304 pre-university students of public schools in Malayer city that had the inclusion criteria were allocated to 2 groups of PMR and control with simple random sampling . Progressive Muscle Relaxation was taught to the intervention group and the students were asked to do the relaxation once a day for one month. Anxiety score of the entire sample was measured at the beginning, during, and the end of the intervention, using the “Beck Depression Inventory”. Data was analyzed using SPSS version 20, and repeated measures test. Results: The mean of the control group›s anxiety score was 14.96 ± 8.22, reaching 16.56 ± 8.08 after 2 weeks and 19.45 ± 8.27 at the end of the fourth weeks. The mean of the intervention group›s anxiety scores was 15.71 ± 8.58. It decreased to 13.33 ± 9.06 at the end of the second week and 10.64 ± 9.30 at the end of the fourth week. The repeated measures test showed a significant difference between the 2 groups in mean anxiety scores (P = 0.008), and was significantly different at the three time points (P < 0.001). Conclusions: The findings of this study showed that the PMR caused a decrease in anxiety in pre-university students.